2019
DOI: 10.1097/aud.0000000000000589
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hearing Loss and Fast-Acting Compression on Amplitude Modulation Perception and Speech Intelligibility

Abstract: Fast-acting compression can restore modulation detection thresholds for listeners with hearing loss to the values observed for listeners with NH. Despite this normalization of the modulation detection thresholds, compression does not seem to provide a benefit for speech intelligibility. Furthermore, fast-acting compression may not be able to restore MDD thresholds to the values observed for listeners with NH, suggesting that the two measures of amplitude modulation sensitivity represent different aspects of te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 51 publications
(55 reference statements)
1
8
0
Order By: Relevance
“…Human-scalp recorded EFRs showed ~10 dB SNR below 100 Hz and fell consistently below the noise floor above 800 Hz. These values are consistent with previous EFR studies in humans (He et al, 2008;Wiinberg et al, 2019).…”
Section: Acknowledgementssupporting
confidence: 93%
“…Human-scalp recorded EFRs showed ~10 dB SNR below 100 Hz and fell consistently below the noise floor above 800 Hz. These values are consistent with previous EFR studies in humans (He et al, 2008;Wiinberg et al, 2019).…”
Section: Acknowledgementssupporting
confidence: 93%
“…In terms of age effects, some studies showed a significant age-related deterioration in AM detection (He et al ., 2008; Füllgrabe et al ., 2015; Wallaert et al ., 2016), while other investigations did not find any effects on AM detection or AM depth discrimination (Schoof and Rosen, 2014; Paraouty et al ., 2016; Schlittenlacher and Moore, 2016; Paraouty and Lorenzi, 2017). Studies comparing listeners with normal hearing to listeners with hearing impairment (referred to hereafter as NH and HI listeners, respectively) have found either similar or lower (i.e., better) AM detection thresholds for the HI listeners (e.g., Moore et al ., 1992, 1996; Moore and Glasberg, 2001; Füllgrabe et al ., 2003; Sek et al ., 2015; Schlittenlacher and Moore, 2016; Wallaert et al ., 2017; Wiinberg et al ., 2019). The observed improvement in AM detection with hearing loss has been suggested to result from the loss of cochlear compression typically associated with sensorineural hearing loss (SNHL; Moore and Oxenham, 1998), which may lead to an increased internal representation of AM depth for HI listeners (Moore et al ., 1996; Jennings et al ., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The observed improvements in consonant recognition performance induced by the proposed envelope expansion schemes were found in a subgroup of the listeners, that is, only selected listeners benefited from this type of processing. Further research is needed to clarify why these differences in benefit occur and to establish to what extent they are related to intersubject variability caused by the experimental design and to what extent these differences can be accounted for by individual differences in psychoacoustic measures, such as temporal envelope detection and discrimination (e.g., Schlittenlacher & Moore, 2016;Wiinberg et al, 2018) or in terms of acclimatization to the processing.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a bandpass-filtered level of 1 dB resulted in an amplification of the output level by 1.3 dB. The value of the scaling factor was based on data from Wiinberg et al (2018). The factor was chosen such that the expansion processing restored the average modulation-depth discrimination performance of the HI listener group to that of the NH listener group at a modulation frequency of 16 Hz.…”
Section: Envelope Expansion Processingmentioning
confidence: 99%
See 1 more Smart Citation